FAKTOR- FAKTOR PENENTU ADANYA AUDIT DELAY - Widhiastuti, Ni Luh Putu; Novitasari, Ni Luh Gde; Adytia, Chintia Jani (Universitas Sangga Buana, 2024)
Audit delay is the length of time needed by an independent auditor to complete his audit work, measured from the closing date of the financial year to the date stated by the independent auditor report. This research aims to determine the effect profitability, solvency, company size, audit committee and auditor turnover on audit delay. The population in this research is banking companies on the Indonesia Stock Exchange for the 2020-2022 period. The sampling method used was a purposive sampling method so that a sample of 44 banking companies was obtained. The analysis technique uses multiple linear regression analysis techniques. The research results show that the company size and audit committee have a negative effect on audit delay. Meanwhile profitability, solvency and Changing auditors has no effect on audit delay.